Young chicks rely on symmetry/asymmetry in perceptual grouping to discriminate sets of elements. Issue 1957 (25th August 2021) - Loconsole, Maria; De Agrò, Massimo; Regolin, Lucia
Abstract : Grouping sets of elements into smaller, equal-sized, subsets constitutes a perceptual strategy employed by humans and other animals to enhance cognitive performance. Here, we show that day-old chicks can solve extremely complex numerical discriminations (Exp.1), and that their performance can be enhanced by the presence of symmetrical/asymmetrical colour grouping (Exp.2 versus Exp.3). Newborn chicks were habituated for 1 h to even numerosities (sets of elements presented on a screen) and then tested for their spontaneous choice among what for humans would be considered a prime and a non-prime odd numerosity. Chicks discriminated and preferred the prime over the composite set of elements irrespective of its relative magnitude (i.e. 7 versus 9 and 11 versus 9). We discuss this result in terms of novelty preference. By employing a more complex contrast (i.e. 13 versus 15), we investigated the limits of such a mechanism and showed that induced grouping positively affects chicks' performance. Our results suggest the existence of a spontaneous mechanism that enables chicks to create symmetrical (i.e. same-sized) subgroups of sets of elements. Chicks preferentially inspected numerosities for which same-sized grouping is never possible (i.e. the prime numerosity) rather than numerosities allowing for symmetrical grouping (i.e. composite).